Prevalence of Vibrio cholerae in cockles in Selangor and Pahang, Malaysia - Ramli, Suzita (2012)
The aim of this study is to determine the presence of Vibrio cholerae in raw cockles (Anadara granosa) sold in wet markets in Selangor and Pahang, Malaysia and to evaluate the survival of V. cholerae using the polymerase chain reaction in combination with the most probable number (MPN-PCR) and the conventional method (growing on the TCBS-biochemical test). In addition, this study attempts to explore the survival of V. cholerae in water, during heat treatment and during the storage of raw cockles. This study is done due to V. cholerae is the etiological agent of cholera which is spread by contaminated food, water or attributed to raw products eaten unprocessed and also commonly found in cockles, thus increase the risk of poisoning potential due to its consumption. A total of 100 samples from 8 different wet markets in Selangor and Pahang were examined for the presence of V. cholerae. The prevalence of Vibrio spp. between the samples from two different sampling areas was not significantly different (p>0.05). In fact, 74% of the samples from Pahang were found positive of Vibrio spp. contrasting to 69% of samples from Selangor, and the prevalence of V. cholerae was also found to be not significantly different between samples from Pahang, 56% and Selangor, 59%. As a comparison, 96% of samples were positive, indicating the detection of V. cholerae using the MPN-PCR method, while only 65% samples were positive when run under the conventional method. The results of the MPN-PCR analysis showed that the positive detection rate was high, while the results of the conventional method were always negative. With MPN-PCR, the load detected in all samples ranged from <30 up to >24000 MPN/g, but most of the samples (24 samples) contained >24000 MPN/g concentration. The enumeration of V. cholerae on TCBS agar was unreliable because of the problem of interference with microflora of similar morphology with V.cholerae that had grown in abundance on TCBS. For the survival of V. cholerae in water, raw cockles (uninoculated raw cockles with V. cholerae) and water (distilled water) samples were determined. V. cholerae can transfer from infected cockles to the surrounding water. The V. cholerae’s load in the samples was 24000 MPN/g on the first day of incubation. The density of V.cholerae’s load in water environment increased from 0 MPN/g to 2400 MPN/g because the pathogens in the cockle samples were transferred to the water. The presence of V. cholerae in distilled water was not only sourced from meat and fluid of infected cockles but also from its shell. In the heat treatment (boiling and grilling) and storage study, two methods of analyses were used, MPN-PCR and conventional method. When boiling the cockles, the result illustrated that there was a significant difference (p≤0.05) for the four temperatures (100 °C, 90 °C, 80 °C and 70 °C) used for both analyses. Cockles need to be cooked for more than 4 minutes in 100 ºC boiling water, 5 minutes in 90 ºC of water and 6 minutes in 80° C, where the pathogen was no longer detected (<1.00 log CFU/g and <1.00 log MPN/g). When heated at 70° C, 9 minutes is sufficient to eliminate the V. cholerae. In the grilling process, there was also a significant difference (p≤0.05) between three temperatures (150 ºC, 200 ºC and 250 ºC) used for both analyses. When cockles are grilled at 150 ºC, they should be cooked for 18 minutes to reduce the V. cholerae’s population to <1.00 log CFU/g and <1.00 MPN/g. Similarly, 12 minutes are needed to grill the cockles at 200 °C and 8 minutes at 250 ºC, where it is sufficient to eliminate the pathogen. For the storage study, the populations of V. cholerae increased when cockles were stored at 10 °C and 28 °C with their shell intact (cockles’ meat with shell) and samples with no shell (cockles’s meat only). However, it decreased gradually when stored at 0 ºC for 16 days. During the storage at 0 ºC, the population of the V. cholerae in unshelled samples decreased and was significantly lower than the shelled samples for both analyses. During storage at 10 ºC for 10 days, it was observed that V. cholerae was able to multiply in both shell and non-shell samples and this shows that 10 ºC storage is not sufficient to inhibit the growth of V. cholerae. The V. cholerae’s load in non-shelled samples, which were stored at 28 ºC for 20 h, increased higher than the shelled samples. As the conclusion, the V. cholerae and Vibrio spp. ‘s loads in cockles are high and the cockles need to be boiled and grilled in sufficient time before consuming, to avoid potential poisoning. In addition, V. cholerae can be transferred easily from infected cockles to the surrounding water and can survive in the storage condition (chilled and ambient temperatures). The combined MPN-PCR method is more effective and accurate for the detection of V. cholerae over the conventional method.